Obsidian from the Neolithic Layers of “Grotta di San Michele Arcangelo di Saracena” (Cosenza), Italy. A Preliminary Report - Forgia Vincenza (De Gruyter, 2021)
The paper presents the results obtained by techno-typological analysis of a lithic assemblage from the Neolithic layers of Grotta San Michele Arcangelo di Saracena (Cosenza) together with the results of micro-wear analysis obtained from a preliminary selection of obsidian artifacts with different provenances distinguished by pXRF analysis. The site provides one of the best preserved Neolithic sequences in the area, from the earliest Impressed Wares (or Impresse Arcaiche) (early sixth millennium BC) to the Spatarella pottery style (end fifth – early fourth millennium BC). Along the Neolithic sequence, it is possible to observe some major changes within lithic resources management. In particular, it is possible to notice some techno-typological breakages between the Early Neolithic and the further stages, until the second phase of the Late Neolithic, when another rupture, corresponding to the Spatarella facies, is evident.